AN EXPERIMENTAL INVESTIGATION OF BEHAVIOR OF ALUMINUM AND MAGNESIUM LAYERS DURING THE ROLLING OF THREE-LAYER STRIPS (Modern Problems of Metallurgy, 2023)
Modern magnesium alloys have prospects for wide application in the automotive and aerospace industries, where the maximum weight reduction of the structure is of great importance. These alloys have a sufficiently high specific strength. But the magnesium alloys that are used are prone to corrosion, which limits their use. One of the options for increasing corrosion resistance is the use of magnesium alloy strips inside three-layer strips, the outer layers of which consist of strips of another metal or alloy. The non-uniformity of the deformation of the strip during rolling affects the formation of the adhesion zone of the layers of different alloys. Therefore, it is relevant to study the deformation of the layers inside such a composite. The purpose of the work is to study the behavior of the layers during the rolling of three-layer bimetallic strips. Three-layer strips made of aluminum alloy AW-2017A and magnesium AZ31, which were obtained by the method of joint hot plastic deformation on a rolling mill, were considered. During hot rolling of three-layer strips, a difference in height relative deformation of layers from different alloys was observed. The study of the behavior of the layers of different metals inside the three-layer strip was performed using an optical microscope. It was established that the outer layers of the AW-2017A alloy are deformed more intensively than the inner layers of the AZ31 alloy when rolling three-layer strips. When deformation of billets with a total initial thickness of 12.8 mm with a degree of deformation of 50%, the relative deformation of aluminum alloy layers is on average 50-52%, and magnesium alloy layers is 44%. For the billet with the initial thickness of the workpiece of 8 mm, a similar ratio is observed in the height deformation of the layers.
Keywords: bimetallic strip; hot rolling; aluminum; magnesium; layer; thickness; deformation.